Quantification of Phenolic and Flavonoid Content, Antioxidant Activity, and Proximate Composition of Some Legume Seeds Grown in Nepal - Khaga Raj Sharma; Govinda Giri (International Journal of Food Science, 2022)
This study was carried out to evaluate some legume seeds growing in Nepal for their proximate composition, quantification of total phenolic (TPC) and flavonoid (TFC) contents, and in vitro, antioxidant and antidiabetic activities. These included legume grains such as chickpeas (Cicer arietinum), pea (Pisum sativum), mung bean (Vigna mungo), lima bean (Phaseolus lunatus), broad bean (Vicia faba), lentil (Lens culinaris), soybean (Glycine max), and common bean (Phaseolus vulgaris). The legume seeds were ground to make the flour which was extracted with methanol. The phenolic and flavonoid content was estimated by Folin-Ciocalteu’s phenol and aluminum chloride colorimetric methods. The in vitro antioxidant and antidiabetic activity was evaluated by using DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging and α-amylase enzyme inhibition assay. The different legumes showed considerable variations in their phenolic contents (30.64±1.50 mg·GAE/g to 46.65±1.25 mg·GAE/g legume seeds). Similarly, the total flavonoid contents showed 135.5±10.88 mg·QE/g to 191.7±8.73 mg·QE/g legume seeds. The in vitro antioxidant activity was evaluated in IC50 which ranged from 31.60±0.06 μg/mL to 69.74±0.89 μg/mL. The α-amylase inhibition was evaluated in IC50 which ranged from 217.38 μg/mL to 425.75 μg/mL as compared to the standard acarbose of 52.76 μg/mL. This study suggested that legumes are good sources of proteins, carbohydrates, and fats mainly for vegetarian people. The selection of the right legume species could be a good source of natural antioxidants and antidiabetics for nutraceutical uses and the beneficial effects of legumes from human health perspectives. Legume seeds growing in Nepal could be used as a sustainable and cheap meat alternative and are considered the most important food source.